Cognitive ontological and orientational metaphors in the Aymara tale “Pani jila sullka” - Mamani Mamani, Alan Ever (2023)
The study aims to analyze the cognitive ontological and orientational metaphors in the aimara tale “Pani jila sullka”. The aforementioned prose corresponds to the book Musphañjama siwsawinaka (2016). In the Aymara tale, various metaphorical expressions classified into two main categories were identified. The first is the ontological metaphor, which includes the expression deities are people. The second is the orientational metaphor, which encompasses expressions such as high status is up and having control or strength is up. To analyze the metaphorical expressions, the hermeneutic method and the data interpretation technique were used. From this result it can be deduced that the Apu represents human behavior in the metaphorical expression of the story, that is, it is a being that transmits vital force. On the one hand, those with more resources show a certain advantage over those with fewer resources. In the same way, a subject with superiority or power dominates a subject without it. The article concludes that there is a need to clarify the animacy that the aimaras show to the deities, as well as the positive and negative behaviors of the aimara-speakers, through the study of metaphors.